POLYHYDROXYLATED CYCLOHEXANE AND CYCLOPENTANE ALPHA-AMINO-ACIDS FROM CYCLIZATIONS OF AN AZIDOLACTONE - Fairbanks, A; Hui, A; Skead, B; Lilley, P; Lamont, R; Storer, R; Saunders, J; Watkin, D; Fleet, G (1994)
Short routes to tetrahydroxylated cyclohexane and cyclopentane α-amino acids with control of the stereochemistry at all 5 carbons bearing functional groups are described from an azidolactone. © 1994.